A Statistical Study of Convicted and Awaiting Trial Individuals in Nigeria (2025) - Ayenigba, Alfred Ayo; Ajao, Olutunde Michael; Augustine, Chinenmerem Darlington (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study examines gender disparities, conviction patterns, and judicial inefficiencies in Nigeria’s correctional system using 2025 data from the Nigerian Correctional Service (NCoS), encompassing 81,200 inmates. Employing a Chi-square Goodness-of-Fit Test, the analysis revealed a stark gender imbalance, with males constituting 97% of inmates versus 50.1% in the general population (χ² = 72,950, p < 0.001), reflecting systemic biases in policing and prosecution. A Chi-square Test of Independence demonstrated a significant association between gender and conviction status (χ² = 62.4, p < 0.001), with 33.7% of males convicted compared to 23.3% of females, while 76.7% of females languished in pre-trial detention. A One-Sample Proportion Test further showed Nigeria’s conviction rate (33%) to be significantly lower than the historical benchmark of 35% (z = -12.5, p < 0.001), highlighting judicial delays and inefficiencies. These findings underscore systemic failures in Nigeria’s criminal justice system, including over-policing of men, prolonged pre-trial detention of women, and chronic case backlogs. The study concludes with urgent recommendations for gender-sensitive reforms, digitized court processes, and alternative sentencing to align practices with human rights standards and reduce overcrowding.